Formulasi dan Uji Aktivitas Sediaan Masker Gel Peel Off Ekstrak Etanol 70% Daun Rambutan (Nephelium Lappaceum L.) Terhadap Propionibacterium Acnes - Rahmawida Putri; Jaka Supriyanta; Dwi Afriliyani Adhil (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Rambutan Leaves (Nephelium Lappaceum L.) one of the plants that contain, alkaloids, flavonoids, tannins and saponins have antibacterial activity against Propionibacterium acnes which is a bacterium that causes acne. Rambutan leaf extract can be formulated to facilitate its use, one of which is in the form of a gel such as a peel off mask. This study aims to determine the characteristics of peel off mask preparations and to determine the antibacterial activity of ethanol extract 70% rambutan leaves (Nephelium Lappaceum L.) Peel off gel mask preparations 70% ethanol extract rambutan leaves (Nephelium Lappaceum L.) formulated into 4 formulas with a variety of extract concentrations, namely F1 (0%), F2 (10%), F3 (15%), F4 (20%). Physical evaluation tests which include: organoleptic, homogeneity, pH, viscosity, dry time, spreadability, adhesion, and irritation. And the antibacterial activity test was carried out against Propionibacterium acnes bacteria using the well method. The results showed that the physical evaluation was said to be good to meet the requirements. Antibacterial test results of gel peel off mask preparation of 70% ethanol extract of rambutan leaves (Nephelium Lappaceum L.) showed the existence of antibacterial activity against Propionibacterium acnes bacteria inhibition was the best at the concentration of F4 (20%) with an average diameter of 10.03 mm. One way ANOVA analiysis result showed that there wewre significant differences in each formula group (p<0,05).